A Numerical Study of Complex Reconstruction in Inverse Elastic Scattering (Communications in Computational Physics, 2020)
The purpose of this paper is to numerically realize the inverse scatteringscheme proposed in [19] of reconstructing complex elastic objects by a single far-fieldmeasurement. The unknown elastic scatterers might consist of both rigid bodies andtraction-free cavities with components of multiscale sizes presented simultaneously.We conduct extensive numerical experiments to show the effectiveness and efficiencyof the imaging scheme proposed in [19]. Moreover, we develop a two-stage technique,which can significantly speed up the reconstruction to yield a fast imaging scheme.